The Use of Optimistic Tone by Ethical Firms’ Leaders - Abdullah Alshorman, Salah Aldain; Saleem Melhem, Yahya (Jordan Journal of Business Administration, 2023)
This study analyzes the annual letter to shareholders of firms that have been recognized for their ethical practices to reveal a verbal tone that can characterize their leaders. This study identifies 63 Chairs/CEOs, representing 63 firms that had been listed among the world’s most ethical companies for three consecutive years (or more). Using DICTION software, their letters were analyzed for five general tones (certainty, activity, optimism, realism and commonality). The comparisons between the whole-sample tone and DICTION’s ’normal range’ of tones shows consistently that their letters to shareholders exhibit a strong tone of optimism, compared to their peers from Fortune 500 companies, social activists, religious leaders and political campaigners.